Susceptibility of eucalyptus species and hybrids to the gall wasp Leptocybe invasa (Hymenoptera: Eulophidae) in northern Misiones, Argentina - Eskiviski, Edgar Rafael; Schapovaloff, Maria Elena; Dummel, Delia Marlene; Fernandez, Margarita M.; Aguirre, Fernando L. (Instituto Nacional de Investigación y Tecnología Agraria y Alimentaria (España), 2022)
Aim of study: To analyze the susceptibility of Eucalyptus and hybrids species to Leptocybe invasa through field assays. Area of study: The north of the Argentine province of Misiones (Colonia Delicia). Material and methods: A total of 11 Eucalyptus species and 2 hybrids were surveyed for damage and severity of L. invasa infestation. Six evaluations were made during an annual period. Main results: The susceptibility ranking to L. invasa from highest to lowest was E. tereticornis > E. propinqua > E. dunni > E. camaldulensis > E. grandis > E. major > E. longistrata >E. grandis × E. camaldulensis. However, E. moluccana, E. urophylla × E. grandis and E. urophylla were tolerant to L. invasa. Research highlights: This study suggests that in Misiones, E. tereticornis is the most sensible eucalyptus species to gall wasp attack, whereas other species and hybrids presented low damage levels or tolerance to L. invasa region.